1997
DOI: 10.1088/0951-7715/10/5/002
|View full text |Cite
|
Sign up to set email alerts
|

How projections affect the dimension spectrum of fractal measures

Abstract: We introduce a new potential-theoretic definition of the dimension spectrum D q of a probability measure for q > 1 and explain its relation to prior definitions. We apply this definition to prove that if 1 < q 2 and µ is a Borel probability measure with compact support in R n , then under almost every linear transformation from R n to R m , the q-dimension of the image of µ is min(m, D q (µ)); in particular, the q-dimension of µ is preserved provided m D q (µ). We also present results on the preservation of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 48 publications
5
94
0
Order By: Relevance
“…Note that because of the convexity of n → ξ n , a necessary and sufficient condition to have multifractal clusters of particles (that is a non-linear dependence of the ζ n ) is that d H < d L and, of course, a value of the Stokes number below the critical clustering value. Hunt & Kaloshin (1997) showed that the dimension spectrum D n of fractal measures defined in the previous subsection is preserved under typical projections when 1 < n 2 ("typical projections" means here almost all of them). From a direct application of this result to the steady-state phase-space density f , one expects that for order-unity values of the Stokes number, ζ n = d−d H +min(n d, ξ n ) for 0 < n 1.…”
Section: Distribution Of Particle Positions At Low Stokes Numbersmentioning
confidence: 92%
“…Note that because of the convexity of n → ξ n , a necessary and sufficient condition to have multifractal clusters of particles (that is a non-linear dependence of the ζ n ) is that d H < d L and, of course, a value of the Stokes number below the critical clustering value. Hunt & Kaloshin (1997) showed that the dimension spectrum D n of fractal measures defined in the previous subsection is preserved under typical projections when 1 < n 2 ("typical projections" means here almost all of them). From a direct application of this result to the steady-state phase-space density f , one expects that for order-unity values of the Stokes number, ζ n = d−d H +min(n d, ξ n ) for 0 < n 1.…”
Section: Distribution Of Particle Positions At Low Stokes Numbersmentioning
confidence: 92%
“…Ballistic motion for St ≫ 1 corresponds to D 2 → 2d, therefore a critical Stokes number St † exists such that D 2 (St † ) = d. The particles' spatial distribution is obtained by projecting the (2 × d)-dimensional phase space onto the d-dimensional physical space. It is tempting to apply a rigorous result on the projection of random fractal sets [22,42] stating that for almost all projections, the correlation dimension of the projected set is related to that of the unprojected one via the relation…”
Section: A Saturation Of the Correlation Dimensionmentioning
confidence: 99%
“…Sauer and Yorke in [SY], and Hunt and Kaloshin in [HK1] and [HK2] investigated transformation of dimensions under typical smooth mappings, also in infinite dimensional spaces. Ledrappier and Lindenstrauss proved in [LL] a result analogous to Theorem 1.1 for measures on Riemann surfaces that are invariant under geodesic flow.…”
Section: Projection Theorem Tells Us That a Is Invisible If And Only mentioning
confidence: 99%